Contraceptive utilization and associated factors among women of reproductive age group in Southern Nations Nationalities and Peoples' Region, Ethiopia: cross-sectional survey, mixed-methods. Issue 1 (December 2017) - Endriyas, Misganu; Eshete, Akine; Mekonnen, Emebet; Misganaw, Tebeje; Shiferaw, Mekonnen; Ayele, Sinafikish
Abstract Background Though contraceptive utilization has comprehensive benefit for women, it was one of underutilized public intervention in Ethiopia and in the study area. Thus, assessing status and factors affecting contraceptive utilization among women of reproductive age group was found key step for program improvement. Methods Community based cross-sectional study was conducted from March to April, 2015 in Southern Nations and Nationalities Peoples' Region, Ethiopia. A multistage stratified cluster sampling method was used to select 3205 study subjects. Study used both quantitative and qualitative methods. Statistical Package for Social Sciences version 20 was used to analyze quantitative data. The association between variables was determined using odds ratio at 95% confidence interval. Results Contraceptive utilization was 53.3% among women of reproductive age groups. Nearly three fourth, (73.6%), of current users were using short-term contraceptive methods. Factors associated with contraception utilization were overall knowledge of and attitude towards contraceptives, age, residence, number of alive children, experience of child death, marital status and deciding number of children. Contraceptive utilization was also affected by various misconceptions. Conclusion Contraceptive utilization was below national Health Sector Development Program IV target. Program implementers need to address socio-cultural barriers. Gender myths and specific roles and power inequalities that can function as a barrier to contraceptive utilization should be assessed.